PENGARUH STRUKTUR MODAL, PROFITABILITAS, KEBIJAKAN DIVIDEN, LIKUIDITAS, UKURAN PERUSAHAAN, STRUKTUR ASET TERHADAP NILAI PERUSAHAAN STUDI PADA PERUSAHAAN MANUFAKTUR TAHUN 2016-2018 - Arini Novandalina; fidyah yuli Ernawati; Marnoto Marnoto (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The value of a company is one of the vital things for a company. Business competition between companies today cannot be separated from the influence of the development of economic dynamics, socio-politics and technological advances. The purpose of this study was to determine whether the capital structure, profitability, dividend policy. Liquidity, firm size and asset structure have an effect on firm value. The population of this research is manufacturing companies in 2016-2018 totaling 163 companies and the sample uses purposive sampling so that the sample is 39